Funkcje społeczne uniwersytetów katolickich - WOJTYŁA, Karol (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
The author analyzes the relationship between the social function of universities and the mission of the Catholic Church by refering to the elementary social bond that constitutes university as such, i.e. the relationship emerging among the individuals who, in a community, pursue the truth. This relationship, and more precisely, respect for the interpersonal bond and for the value of truth, provides the founda− tion and justification for the principle of autonomy of universities, at the same time pointing to the Gospel. It is there, in the relationship between Teacher−Master and His disicples, that the author finds the roots of universities and their function. Especially Catholic universities participate in the mission of the Church in the way specific to a community in pursuit of truth, namely through dialogue. Summarized by Patrycja Mikulska So−far unpublished lecture delivered at the Catholic University of Lublin on 27 April 1968. Source: The typescript of the lecture comes from in the private archives of Fr. Tadeusz Styczeń, SDS, and is currently part of the library collection of the John Paul II Institute at the John Paul II Catholic University of Lublin.